Urinary metabolic profiling of cisplatin nephrotoxicity andnephroprotective effects of Orthosiphon stamineus leaves elucidatedby1H NMR spectroscopy - Pariyani, Raghunath; Ismail, Intan Safinar; Azam, Amalina; Khatib, Alfi; Abas, Faridah; Shaari, Khozirah; Hamza, Hazilawati (Elsevier, 2017)
Orthosiphon stamineus (OS) is a popular medicinal herb used in traditional Chinese medicine as a diureticagent and for renal system disorders. This study employed1H NMR based metabolomics approach toinvestigate the possible protective activity of OS in cisplatin induced nephrotoxicity owing to its diureticand antioxidant activities. Aqueous (OSAE) and 50% aqueous ethanolic (OSFE) extracts of OS leaveswere orally administered at 400 mg/kg BW doses to rats which were then intraperitoneally injectedwith cisplatin at 5 mg/kg BW dose. The1H NMR profile of the urine samples collected on day 5 aftercisplatin administration were analyzed by multivariate pattern recognition techniques, whereby 19marker metabolites suggestive in the involvement of TCA cycle, disturbed energy metabolism, alteredgut microflora and BCAA metabolism pathways were identified. It was observed that OSFE caused sig-nificant changes (p < 0.05) in the levels of 8 markers namely leucine, acetate, hippurate, lysine, valine,2-oxoglutarate, 3-HBT and acetoacetate resulting in a moderate ameliorative effect, however, it did notcompletely protect from nephrotoxicity. OSAE did not demonstrate significant down regulatory effectson any markers, albeit, it potentiated the cisplatin nephrotoxicity by inducing significant increase in glu-cose, glycine, creatinine, citrate, TMAO, acetate and creatine levels. A Principal Component Analysis (PCA)of the1H NMR spectra of OS extracts identified that OSFE had higher concentrations of the secondarymetabolites such as caffeic acid, chlorogenic acid, protocatechuic acid and orthosiphol, among others.Whereas, OSAE was characterized by higher concentrations of acetate, lactate, succinic acid, valine andphosphatidylcholine. This research denotes the first comprehensive analysis to identify the effects of OSextracts on cisplatin nephrotoxicity.